(untitled) (Nigerian Journal of Technology, 2016)
Information on chemical properties of fruits is crucial in processing it into different foods. Mechanical properties of fruits determine their susceptibility to mechanical damages that occur during harvest, transportation, and storage; and which eventually lead to a pronounced reduction in commercial value. This study was conducted to investigate the chemical and mechanical properties of unshelled (black), shelled (yellow) and kernel of Dialium guineense fruit. The chemical properties investigated include some proximate and mineral elements. The mechanical properties were bio-yield force, rupture force, deformation at rupture point, deformation ratio at rupture point, compressive strength and total strain energy. The fruit pulp was found to be composed of protein (9.4%), carbohydrate (75%), crude fat (5.2%), crude fibre (4.6%), and ash content (2.4%) at 19% moisture content (wb). The mineral composition of the pulp were sodium (3.2 g/kg), magnesium (2.9 g/kg), phosphorus (0.5 g/kg), calcium (0.5 g/kg), iron (0.1 g/kg), and vitamin C (0.3 g/kg) at a pH of 3.9. Less force is required to crack the fruit across the length, followed by across the thickness and then across the width. Velvet tamarind (Dialium guineense) fruit pulp is a promising source of food and essential minerals due to its nutritional values, hence facilitating its postharvest processing is inevitable. http://dx.doi.org/10.4314/njt.v36i1.30